2020
DOI: 10.1016/j.enconman.2020.113083
|View full text |Cite
|
Sign up to set email alerts
|

Hydration state diagnosis in fractal flow-field based polymer electrolyte membrane fuel cells using acoustic emission analysis

Abstract: Techniques for evaluating water management are critical to diagnose the performance of polymer electrolyte membrane fuel cells (PEMFCs). Acoustic emission as a function of polarisation (AEfP) has been recently introduced as a non-invasive, non-destructive method to analyse the water generation and removal inside a PEMFC during polarisation. AEfP was shown to provide unique insight into water management within a conventional PEMFC and correlating it to cell performance. Here, AEfP is used to characterise the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Based on the 50 × 50 mm 2 conventional interdigitated flow field, a new standard size ADFF model was established (Figure 3c). The ADFF is provided with two reaction gas inlets (1), left and right inlet channels (2), AD inlet (3), serpentine drainage channel (4), and outlet (5). The inlet channels are an interdigitated structure distributed on both sides, and the outlet channel is a serpentine structure distributed between the two sides of the inlet channels as the reaction gas outlet channel.…”
Section: Numerical Simulation Of Single Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the 50 × 50 mm 2 conventional interdigitated flow field, a new standard size ADFF model was established (Figure 3c). The ADFF is provided with two reaction gas inlets (1), left and right inlet channels (2), AD inlet (3), serpentine drainage channel (4), and outlet (5). The inlet channels are an interdigitated structure distributed on both sides, and the outlet channel is a serpentine structure distributed between the two sides of the inlet channels as the reaction gas outlet channel.…”
Section: Numerical Simulation Of Single Cellmentioning
confidence: 99%
“…Therefore, forced convection once was a research hotspot because of its unique mass transfer mode, which is more conducive to water management within PEMFCs. 1 5 There are a number of studies in which the blocks and baffles were added in the flow field. 6 11 The results showed that the blocks improved the current density and heat and mass transfer efficiency, and the shape and layout of the blocks significantly influenced performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cell dehydration at 60 °C was confirmed by the larger Ohmic resistances measured, which were ~30% larger than those measured at 45 °C, as reported in (24). It has been identified that acoustic activity from PEMFCs can be utilized to establish the hydration conditions inside the fuel cell, as reported in (24,25). Physical impact events created by the release of water into flow-fields result in the generation of AE and the corresponding intensity of such impacts is measured by the amplitude (dB) of AE signals detected.…”
Section: Resultsmentioning
confidence: 60%
“…Furthermore, the measured AE energy was utilized for correlating the level of cell polarization with the liquid water generation and removal within flow-fields. This study (24) was instrumental in evaluating the performance of two different fractal flow-field PEMFCs, reported in Bethapudi et al (25), where flooding and normal operating conditions were diagnosed in 2-way and 1way fractal flow-fields, respectively, using AE metrology.…”
Section: Introductionmentioning
confidence: 99%
“…AE amplitude, counts and energy accumulation). [18][19][20][21] Specifically, in comparison with conventional monitoring approaches, an important characteristic of acoustic emission technology is that AE signals generally generate by damage defects, among which crack propagation is commonly used as signal source. [22][23][24][25] Thus, the reliability of the monitoring results depends on the effective analysis of the AE characteristics of the structures under different working conditions.…”
Section: Introductionmentioning
confidence: 99%